2023
DOI: 10.3390/nu15143165
|View full text |Cite
|
Sign up to set email alerts
|

Association between the Consumption of Ultra-Processed Foods and Asthma in Adults from Ribeirão Preto, São Paulo, Brazil

Abstract: Background: Ultra-processed Food (UPF) consumption can play a role in the pathogenesis and progression of asthma. The aim of this study was to evaluate the association between the consumption of UPF and asthma. Methods: This cross-sectional study included 1857 adults aged 23–25 years from the Ribeirão Preto-SP birth cohort (1978/1979). The exposure variable was the consumption of UPF (expressed as their percentage contribution to energy intake—% total caloric value [%TCV] and their percentage contribution to t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 40 publications
0
1
0
Order By: Relevance
“…Recent studies suggest that the interaction between obesity and asthma is more complex than has been reported, and there is not a simple association between excess weight and asthma. Despite the fact that we have found few studies indicating that evidence between UPF consumption and asthma cannot be fully demonstrated [48], most studies can justify an association between UPF consumption and asthma by different plausible mechanisms. Related to this, there are studies on the characteristics of the diet [49] or the exposure to some chemical compounds and pollutants that can also explain the association between obesity and asthma [50].…”
Section: Western Diet As a Risk Factor For Asthmamentioning
confidence: 80%
“…Recent studies suggest that the interaction between obesity and asthma is more complex than has been reported, and there is not a simple association between excess weight and asthma. Despite the fact that we have found few studies indicating that evidence between UPF consumption and asthma cannot be fully demonstrated [48], most studies can justify an association between UPF consumption and asthma by different plausible mechanisms. Related to this, there are studies on the characteristics of the diet [49] or the exposure to some chemical compounds and pollutants that can also explain the association between obesity and asthma [50].…”
Section: Western Diet As a Risk Factor For Asthmamentioning
confidence: 80%